1986
DOI: 10.1007/bf01318690
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological characterization of intraepithelial and lamina propria lymphocytes in control ileum and colon and in inflammatory bowel disease

Abstract: Using monoclonal antibodies to T and B lymphocytes, to natural killer cells, and to HLA-DR antigen, we characterized the lymphocyte population within the epithelial and lamina propria regions in control intestine and colon, and in grossly involved and in grossly uninvolved intestine and colon of patients with active inflammatory bowel disease. There were significantly more intraepithelial T cells in control ileum than in control colon. In comparison to control, there was a heterogeneity of alterations in intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
54
1
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 25 publications
13
54
1
3
Order By: Relevance
“…Currently, it is reported that UC symptoms arise due to a speciˆc autoimmune reaction in the large intestine. 21) However, despite many reports on UC research, the determining factor for UC progression has not been clariˆed. Therefore various studies have been performed using UC animal models in attempts to elucidate the cause of UC and establish a treatment for it.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is reported that UC symptoms arise due to a speciˆc autoimmune reaction in the large intestine. 21) However, despite many reports on UC research, the determining factor for UC progression has not been clariˆed. Therefore various studies have been performed using UC animal models in attempts to elucidate the cause of UC and establish a treatment for it.…”
Section: Discussionmentioning
confidence: 99%
“…In normal subjects, 80 -90% of colonic and ileal intraepithelial lymphocytes are T cells (9,10), and 5-40% of these are of the ␥␦ subtype (11). Mosnier et al (12) showed that the colonic intraepithelial lymphocytes in lymphocytic and collagenous colitis are CD3ϩ/CD8ϩ T cells.…”
mentioning
confidence: 99%
“…44 In fact, experimental human and animal studies have shown that enteric glial cells may also be involved in intestinal inflammation, 45,46 enteric neurotransmission [47][48][49] and, importantly, are essential for the homeostasis of enteric neurons. 50 With respect to this last aspect, a recent study showed that enteric glia disruption may alter the neurochemical coding of enteric neurons in an experimental animal model.…”
Section: Discussionmentioning
confidence: 99%